The Right of Suspects to Obtain Legal Aid in Criminal Investigation - Imanuel Marthen Dumais; Muhadar Muhadar; Marwati Riza (Musamus Law Review, 2018)
In the law enforcement aspect, the unfair treatment of suspects is an act of public scrutiny that falls into the category of human rights violations. This study aims to analyze the urgency of the fulfillment of suspect rights at the stage of investigation as well as the implementation of the right to obtain legal assistance for the suspect at the investigation stage. The type of research is sociolegal research. This research conducted in Manokwari, West Papua, Indonesia, precisely in Manokwari Police Station. The result of the research indicates that the urgency to fulfill the rights of suspects is in the framework of the protection of the rights of the community which is the basic right if not fulfilled is discrimination and injustice which is expressly prohibited under the 1945 Constitution. Implementation of the right to obtain legal aid for the suspect at the investigation stage at Polres Manokwari has not been implemented optimally. The low interest of the suspects to be accompanied for not understanding the urgency of legal aid and the assumption that the use of legal aid services should be charged to be one of the obstacles in the fulfillment of the rights of suspects. In addition, the existence and interest of advocates on the provision of legal assistance is still very minimal also a constraint in implementing the right to obtain legal assistance for the suspect.